Preservation of Local Culture Through Community Service Programs in Bukit Sangkal Village - Khalid Andri; Rendi Arifin; Omar Ahmad (Pengabdian: Jurnal Abdimas, 2025)
Background. The rapid pace of modernization and urbanization has contributed to the erosion of local cultural heritage, especially in rural communities such as Bukit Sangkal Village, South Sumatra. Cultural practices, traditional arts, and indigenous values are increasingly marginalized in favor of more dominant globalized norms. Purpose. This study aims to examine how community service programs initiated by higher education institutions can play a pivotal role in preserving and revitalizing local culture. Method. Using a qualitative participatory action research (PAR) method, the study engaged directly with local stakeholders, including elders, artisans, youth groups, and village leaders. Data were collected through focus group discussions, field observations, and documentation of cultural activities.Results. The findings reveal that collaborative cultural workshops, educational campaigns, and documentation of oral traditions significantly increased awareness and participation among local residents. The revitalization of traditional dance and craft-making practices was particularly effective in engaging the younger generation. Conclusion. The study concludes that community service programs can act as dynamic instruments of cultural preservation when they are participatory, adaptive, and context-sensitive. These programs not only preserve heritage but also strengthen communal identity and intergenerational transmission of cultural knowledge.